The "Man of God": Understanding Biblical Influence on Contemporary Mega-Church Prophets in Zimbabwe - Machingura, Francis (Prophets, Profits, and the Bible in Zimbabwe: Festschrift for Aynos Masotcha Moyo, 2013)
Different names are used to refer to various religious functionaries across the World Religions. In Zimbabwean Christianity, there is a group of Christian officials who are currently popularly known as “men of God.” This article argues that this title is one of the many influences of the Bible on contemporary Christianity, since its use is dependent on its biblical usage, especially regarding the extra-ordinary and miraculous events surrounding Elijah and Elisha. The title is used eighty times in the Christian Bible and seventy-nine of these are in the Old Testament. In our analysis of both its Old Testament and contemporary usage, the title is used to acknowledge the qualitative difference between all human beings and the few men (and women) who are specially chosen to be God’s representatives. These specially chosen functionaries are more than simply human, and do more than simple human beings do. “Man of God” is understood as a continuation of biblical traditions.
free